Identification of the acinetobacter baumannii ribonuclease p catalytic subunit: Cleavage of a target mRNA in the presence of an external guide sequence - Davies Sala, Carol Giselle (2018)
The bacterial ribonuclease P or RNase P holoenzyme is usually composed of a catalytic RNA subunit, M1, and a cofactor protein, C5. This enzyme was first identified for its role in maturation of tRNAs by endonucleolytic cleavage of the pre-tRNA. The RNase P endonucleolytic activity is characterized by having structural but not sequence substrate requirements. This property led to development of EGS technology, which consists of utilizing a short antisense oligonucleotide that when forming a duplex with a target RNA induces its cleavage by RNase P. This technology is being explored for designing therapies that interfere with expression of genes, in the case of bacterial infections EGS technology could be applied to target essential, virulence, or antibiotic resistant genes. Acinetobacter baumannii is a problematic pathogen that is commonly resistant to multiple antibiotics, and EGS technology could be utilized to design alternative therapies. To better understand the A. baumannii RNase P we first identified and characterized the catalytic subunit. We identified a gene coding for an RNA species, M1Ab, with the expected features of the RNase P M1 subunit. A recombinant clone coding for M1Ab complemented the M1 thermosensitive mutant Escherichia coli BL21(DE3) T7A49, which upon transformation was able to grow at the non-permissive temperature. M1Ab showed in vitro catalytic activity in combination with the C5 protein cofactor from E. coli as well as with that from A. baumannii, which was identified, cloned and partially purified. M1Ab was also able to cleave a target mRNA in the presence of an EGS with efficiency comparable to that of the E. coli M1, suggesting that EGS technology could be a viable option for designing therapeutic alternatives to treat multiresistant A. baumannii infections.